Cervical Sagittal Alignment in Patients With Basilar Invagination. Issue 21 (1st November 2022) - Zhou, Yang; Hou, Juedong; Xiao, Ruipei; Zheng, Jintao; Zou, Xiaobao; Zhu, Yongjian; Yao, Ling; Chen, Jianting; Ma, Xiangyang; Yang, Jincheng
Abstract : Study Design: Retrospective study. Objective: To present a morphological map of cervical sagittal alignment in basilar invagination (BI), a congenital anomaly of the craniovertebral junction, and contribute to a comprehensive understanding of cervical sagittal alignment in congenital cervical deformities. Summary of Background Data: Ideal cervical sagittal alignment and surgical targets are debated by scholars. However, most of the literature focuses on the description of cervical sagittal alignment in acquired cervical diseases and normal subjects and few on congenital cervical spine deformities. Materials and Methods: This study analyzed cervical spine lateral radiographs of 87 BI patients and 98 asymptomatic subjects. They were analyzed for cranial, cervical spine, and thoracic inlet parameters. Results: Patients with BI manifested significantly larger values for the following parameters than asymptomatic subjects: cranial tilt, cranial incidence angle, sagittal vertical axis (SVA) CGH–C7, C2–C7 angle, cervical tilt, and significantly smaller values for the following parameters: cranial slope, C0–C2 angle, C0–C7 angle, SVA C2–C7, spine tilt, thoracic inlet angle, and neck tilt. In the BI group, SVA C2–C7 was the cervical parameter most strongly correlated with the cranial, cervical spine, and thoracic inlet parameters, and was smaller in BI patients with fusion (atlanto-occipital assimilation) than in those without. Conclusion: A significant difference was observed between BI patients and asymptomatic subjects. BI patients have craniums tilted forward and downward, smaller upper cervical lordosis, larger lower cervical lordosis, and smaller thoracic inlet angle. In BI patients, the SVA C2–C7 is an important parameter in cervical sagittal alignment. In both individuals with congenital anomalies of the craniovertebral junction and the asymptomatic population, cervical spine alignment is significantly associated with cranial alignment, particularly thoracic inlet alignment.